Assessing Language Skills in Bilingual Children: Current Trends in Research and Practice - Freeman, Max R.; Schroeder, Scott R. (Journal of Child Science, 2022)
A continuously challenging issue in the field of speech–language pathology is accurately identifying and diagnosing a language disorder in school-aged (pre-kindergarten through 5th grade) bilingual children, as bilingual children are disproportionately under- and overidentified with a language disorder. The current review focuses on the assessment of bilingual children in pre-kindergarten through fifth grade, aimed to inform teachers, pediatricians, parents, and other relevant professionals of issues surrounding assessment of these dual-language learners. We examine the barriers to assessing bilingual children for language disorders, such as the lack of availability of bilingual tests, underinformative current best practice guidelines, lack of speech–language pathologist (SLP) training/knowledge of bilingualism, and use of interpreters. We discuss the necessary considerations when SLPs use norm-referenced tests with bilingual children, such as norming samples, accurate identification of a language disorder, reliability and validity, test administration, and potential solutions to using otherwise poorly suited norm-referenced tests. We also consider research on several alternative measures to norm-referenced assessments, including dynamic assessment, nonword repetition, language sampling, nonlinguistic cognition, and parent report. We conclude by synthesizing the information in this review to offer six principles of best practices for bilingual assessment.
Keywords: language assessment; bilingual; children; developmental language disorder; language impairment